Nitroxoline is a novel inhibitor of NLRP3-dependent pyroptosis - Christina Maeder; Roberto Baumann; Susanne Gaul; Sven Fikenzer; Michael Schaefer; Hermann Kalwa; Ulrich Laufs; Alexander Kogel (Cell Death Discovery)
Abstract Aberrant activity of the NLR family pyrin domain containing 3 (NLRP3) inflammasome contributes to a wide range of diseases associated with acute inflammatory responses and chronic sterile inflammation. Activation of the NLRP3 inflammasome mediates pyroptotic cell death and the release of pro-inflammatory cytokines. To date, no selective inhibitor of inflammasome activity is available for the use in humans. We conducted a medium-throughput screening of 6280 drugs or drug-like compounds and identified novel inhibitors of the NLRP3 inflammasome. Among these, nitroxoline was further characterized because the drug is approved for antibiotic treatment in humans, and we found no toxicity over a wide range of concentrations. Treatment of THP-1 monocytes with 80 μM nitroxoline markedly reduced the secretion of the pro-inflammatory cytokine Interleukin-1β (IL-1β) by 95% from 197.8 pg ml−1 to 11.0 pg ml−1. Nitroxoline reduced downstream events of inflammasome activation including caspase-1 activity (FAM-Flica+/7AAD+ cells control 57.1 ± 9.4% vs. nitroxoline 27.9 ± 15.5%) and gasdermin D cleavage (ratio cleaved/uncleaved control 8.7 ± 4.3 vs. nitroxoline 1.3 ± 1.3, p < 0.05). The data were confirmed in cultured human PBMC, where nitroxoline abrogated IL-1β secretion. Mechanistically, drug affinity-responsive target assays revealed that nitroxoline directly interacts with the NACHT domain of NLRP3, inhibiting inflammasome assembly. Nitroxoline did not affect NF-κB-dependent gene expression, as analyzed by nuclear p65 translocation and IκBα phosphorylation, and did not inhibit the NLR-family member NLRC4 or the AIM2 inflammasomes, indicating specificity for NLRP3. Nitroxoline is a novel inhibitor of the NLRP3 inflammasome, which reduces inflammasome assembly and IL-1β release. These data set the stage for testing the effects of nitroxoline on sterile inflammation in clinical studies.